Efforts to Develop Tourism Villages in Badung Regency - Made Dewi Jayanti; Ida Ayu Putu Sri Widnyani; I Gede Wirata (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This article begins with the fact that the tourist villages (11 tourist villages that have a Regent's Decree) in Badung Regency are not evenly distributed in tourism development according to their potential. The problems in this research include (1) What are the basic problems in developing Tourism Villages in Badung Regency?; and (2) What are the efforts to develop Tourism Villages in Badung Regency in the future? This research uses a qualitative research type and approach. The reason for using a qualitative research design is because essentially it is observing people in their living environment, which in this case is the community around the Tourism Village area in Badung Regency. The data analysis technique used was qualitative data analysis techniques with an interactive model from Miles and Huberman. The results of the research show (1) The basic problem of developing tourist villages in Badung Regency includes tourist villages in Badung Regency, namely the wrong perspective regarding the existence of tourist villages which are still minimal, simply following the program launch, and waiting to be moved. When there is an event or work program from the provincial or central government, the Pokdarwis is directed by the Badung district government to prepare and implement it. After the event passed, the tourist villages seemed to be left alone and would repeat the same case; and (2) Efforts to develop tourist villages in Badung Regency in the future should pay attention to the local community's understanding of tourist villages through a planned and measurable socialization process so that the stipulation of a Tourism Village Decree from the district government is not in vain, because once the Tourism Village Decree is established then the village is ready in terms of planning, management and development, capital, optimizing tourism potential, the role of local government, tourism stakeholders/practitioners, NGOs, mentoring patterns, human resources, cooperation, marketing strategies.